Supernumerary centrosomes nucleate extra cilia and compromise primary cilium signaling - Mahjoub, Moe R. (2012)
The primary cilium is a nexus of cell signaling, and ciliary dysfunction is associated with polycystic kidney disease, retinal degeneration, polydactyly, neural tube defects, and obesity (ciliopathies) [1]. Signaling molecules for cilium-associated pathways are concentrated in the cilium, and this is essential for efficient signaling. Cilia are nucleated from centrioles, and aberrant centriole numbers are seen in many cancers and in some ciliopathies [2]. We tested the effect of supernumerary centrioles on cilium function, and found that cells with extra centrioles often formed more than one cilium, had reduced ciliary concentration of Smoothened in response to Sonic hedgehog stimulation, and reduced Shh pathway transcriptional activation. This ciliary dilution phenotype was also observed with the serotonin receptor Htr6, fibrocystin PKHD1, and Arl13b. The presence of extra centrioles and cilia disrupted epithelial organization in 3-D spheroid culture. Cells mutant for the tuberous sclerosis gene Tsc2 also had extra cilia and diluted ciliary protein. In most cells extra cilia were clustered and shared the same ciliary pocket, suggesting that the ciliary pocket is the rate-limiting structure for trafficking of ciliary proteins. Thus, extra centrioles and cilia disrupt signaling, and may contribute to disease phenotypes.